Student attitudes, performance and satisfaction towards academic research in Institute Kemahiran Mara Bintulu, Sarawak / Alexander Abat - Abat, Alexander (2019)
This research was attempted to investigate student’s attitude, performance, satisfaction towards academic research in Institute Kemahiran Mara Bintulu, Sarawak. The intention of this research to examine the relationship between students’ attitude towards academic research and performance and also satisfaction. This study also identified whether is there any relationship between students' attitude towards academic research and performance and satisfaction. Pilot testing was earned out to certify the reliability of the questions before final distribution. For the pilot test 30 questionnaire were distributed. There are a total of 210 sets of questionnaire being distributed to students in Institute Kemahiran Mara, Bintulu, Sarawak.